Disrupting a Delicate Balance: The Allied Blockade Policy and the Law of Maritime Neutrality during the Great War. (23rd July 2018) - Neff, Stephen C
Abstract: The law of neutrality as it stood in 1914 was a set of compromises that had evolved from past practices, most notably regarding the law of blockade. During World War I, the Allied (predominantly British) economic warfare policy could not comprise classic close blockading as in previous conflicts. As a result, various specific policies were devised that, in combination, were designed to have much the same material impact and, therefore, to operate as a functional equivalent to traditional blockading. The lawfulness of each of these component policies was determined by the law of neutrality as it had evolved up to 1914, as embodied most notably in the (unratified) Declaration of London of 1909. Six major legal strategies were devised. Contraband lists were expanded beyond the limits stated in the Declaration, enabling goods to be captured anywhere on the high seas. There was also a reclaiming of traditional, pre-Declaration rights, amounting effectively to a repudiation of the compromises and concessions that had gone into the making of the Declaration. The use of existing traditional belligerents' rights was extended, most notably in the area of visit and search. Rigorous use was made of the continuous-voyage principle, most notably with the application of the principle to conditional, as well as to absolute, contraband (contrary to the terms of the Declaration of London). The principle of reprisal was invoked to justify measures that were barred by the inherited law of neutrality. Finally, various sovereign-right measures were employed, most notably navicerting and blacklisting. Debates over the lawfulness of these measures occurred during the conflict and continued afterwards. The basic conflict was between a focus on the adherence to specific rules and a focus on the adherence to the deeper principles that arguably underlay the surface rules.